Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1002/app.1993.070480815
|View full text |Cite
|
Sign up to set email alerts
|

Modeling poly(vinyl alcohol)‐stabilized vinyl acetate emulsion polymerization. II. Comparison with experiment

Abstract: SYNOPSISThe mathematical model presented in Part I, accommodating the emulsion polymerization of vinyl acetate stabilized with poly (vinyl alcohol), predicts experimental conversion and particle size data with reasonable accuracy. Model predictions of measurable variables exhibit sensitivity to variables affecting either primary ungrafted particle nucleation or flocculation kinetics, but are relatively insensitive to variables affectingpoly (vinyl alcohol) grafting reactions and the resulting primary grafted p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…The 7-m 3 reactor is continuously stirred. The use of a polymeric emulsifier affects the kinetics of the reaction and the mechanism of stabilization of the particles [20,21]. It also increases the rate of thermal decomposition [23,24].…”
Section: The Processmentioning
confidence: 99%
See 1 more Smart Citation
“…The 7-m 3 reactor is continuously stirred. The use of a polymeric emulsifier affects the kinetics of the reaction and the mechanism of stabilization of the particles [20,21]. It also increases the rate of thermal decomposition [23,24].…”
Section: The Processmentioning
confidence: 99%
“…As the objective of this model was to show the influence of the polymerizable surfactant, other aspects, such as the balance of the number of particles, were modelled less rigorously. Gilmore et al [20,21] presented, in 1993, the first model in which grafting onto the polyvinyl alcohol backbone during nucleation was considered. Arau´jo and Giudici [22] developed a model intended for optimization, considering a non-polymerizable emulsifier.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the presence of a large monomer/H 2 O interface area is essential for PVOH grafting to create a PVOH‐stabilized acrylic latex. Gilmore et al7, 8 used mathematical modeling to explore the kinetics of VAc emulsion polymerization in the presence of PVOH. They inferred that grafting in the nucleation stage is not very important.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer films obtained from the latices prepared in the presence of poly(vinyl alcohol) re-sulted in higher tensile strengths than of those prepared with only nonylphenol ethoxylates, presumably due to the formation of a reinforcing poly(vinyl alcohol) structure. 22 Gilmore et al modeled poly(vinyl alcohol)-stabilized semicontinuous VAc emulsion polymerization 23 and compared their model with experimental findings. Their model suggests that, when the molar ratio of VAc to poly(vinyl alcohol) is high, physical adsorption of poly(vinyl alcohol) onto the latex particle is a more important process than is grafting.…”
Section: Introductionmentioning
confidence: 99%
“…Their model suggests that, when the molar ratio of VAc to poly(vinyl alcohol) is high, physical adsorption of poly(vinyl alcohol) onto the latex particle is a more important process than is grafting. 23 In our work, the effect of the ethoxylation degree of ethoxylated nonylphenol nonionic emulsifiers in the semicontinuous emulsion polymerization of the VAc monomer in the presence of 88% of a hydrolyzed poly(vinyl alcohol) colloid stabilizer was examined to determine the effect to the final latex viscosity, average polymer molecular weight, polymer grafting degree, latex surface tension, and surface free energy of the dried films.…”
Section: Introductionmentioning
confidence: 99%